2022
DOI: 10.1007/s11469-022-00909-8
|View full text |Cite
|
Sign up to set email alerts
|

Work Addiction and Depression, Anxiety, and Stress: the Mediating Role of Food Addiction Among Lebanese Young Adult Workers

Abstract: Work addiction is considered a public health concern, as it can lead to negative and harmful health outcomes. However, patterns leading from work addiction to mental health concerns remain so far largely unknown and under-studied. We aimed to verify whether the relationship between work addiction and psychological distress (i.e., depression, anxiety, and stress) is mediated by food addiction among young adult workers in the context of Lebanese culture. The second objective was to validate the Arabic version of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 103 publications
1
5
0
Order By: Relevance
“…For example, hyper-engagement in work could cause social function disturbance and even physical illness. Chronic stress as a consequence of WA may lead to other disorders, including depression, anxiety, and substance use disorders, such as nicotine dependence and alcohol or sedative abuse ( American Psychiatric Association, 2013 ; Hauk and Chodkiewicz, 2013 ; Durand-Moreau et al, 2018 ; Kang, 2020 ; Kun et al, 2020 ; Cossin et al, 2021 ; Li et al, 2021 ; Eason et al, 2022 ; Fekih-Romdhane et al, 2022 ; Zeng and Liu, 2022 ). Hence, screening for WA can help to protect social workers’ physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hyper-engagement in work could cause social function disturbance and even physical illness. Chronic stress as a consequence of WA may lead to other disorders, including depression, anxiety, and substance use disorders, such as nicotine dependence and alcohol or sedative abuse ( American Psychiatric Association, 2013 ; Hauk and Chodkiewicz, 2013 ; Durand-Moreau et al, 2018 ; Kang, 2020 ; Kun et al, 2020 ; Cossin et al, 2021 ; Li et al, 2021 ; Eason et al, 2022 ; Fekih-Romdhane et al, 2022 ; Zeng and Liu, 2022 ). Hence, screening for WA can help to protect social workers’ physical and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Andreassen and colleagues found that the BWAS has a unidimensional structure with all items loading in one factor, work addiction. BWAS also has previously been validated in other countries, such as Italy, and the BWAS has been used successfully in prior studies to measure work addiction ( Molino et al, 2002 ; Andreassen et al, 2016 ; Atroszko et al, 2016 ; Lichtenstein et al, 2019 ; Fekih-Romdhane et al, 2022 ). The original English-language BWAS has been used to help workers make adjustments to protect their health.…”
Section: Introductionmentioning
confidence: 99%
“…However, the network approach’s impact on work addiction research should not be overestimated. The network framework allows to investigate direct relationships between symptoms of work addiction easily, but a careful examination of previous research grounded in the latent variable framework may lead to somewhat similar observations (Atroszko et al, 2017; Bellali et al, 2023; Denizci Nazlıgül et al, 2022; Falco et al, 2022; Fekih-Romdhane et al, 2022; Molino et al, 2022). Additionally, the moderate level of symptom predictability indicates that a substantial portion of work addiction symptoms’ variability cannot be predicted based on states of other symptoms.…”
Section: Conclusion and Future Studies Directionsmentioning
confidence: 99%
“…The correlation between mood modification (3) and withdrawal (5) was required in Turkey (Denizci Nazlıgül et al, 2022). The correlation between conflict (6) and problems (7) was required in Turkey (Denizci Nazlıgül et al, 2022) and Lebanon (Fekih-Romdhane et al, 2022). In this paper, we hypothesize that these relationships may indicate the inadequacy of the latent variable framework to capture the direct relationships between symptoms postulated by the network theory of mental disorders (Borsboom, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While excessive work engagement may yield positive outcomes like high productivity, it often comes at the expense of personal relationships and well-being. Moreover, emphasising the positive aspects may underestimate the potential negative impacts on physical and psychological health, as research consistently links workaholism to higher levels of stress, burnout, and health issues ( Andreassen et al, 2018;Fekih-Romdhane et al, 2022;Makhdoom et al, 2022). This implies the cruciality of recognising the thin line between high engagement and unhealthy overworka balanced approach that promotes well-being and productivity without crossing into compulsive work behaviours.…”
Section: Introductionmentioning
confidence: 99%